Sistem Camera Dan Pengamanan Kotak Amal Berbasis Internet Of Things Dan Telegram - Imam Fahmi Udin Ma'ruf; Jamaaluddin; Izza Anshory (SinarFe7, 2022)
Theft in a place of worship is a crime by stealing things that are not privately owned but public property without permission and these activities are carried out from religious places such as mosques, churches and monasteries. The theft of charity box funds is an interesting topic for some people and the mosque manager personally in particular, considering that charity box funds are general funds intended for the renovation or purchase of mosque needs and the needs of religious events. By using a microcontroller as an auxiliary component to monitor valuables. This microcontroller control system can be used to secure charity box funds in any mosque equipped with a security feature based on Selenoid door locks that can only be opened by ESP 32-CAM and using a vibration sensor will detect shocks and a buzzer will sound. sounds like an alarm for Telegram to alert the Mosque management in the event of the forced destruction of the charity box. The camera system and security for charity boxes based on the internet of things and telegrams are expected to minimize the occurrence of acts of theft and increase security not only at places of worship but can also be used as storage places for valuables.